Talking about Health A Philosophical Dialogue - Nordenfelt, Lennart (Value Inquiry Book Series ;, 1997)
This book is a scholarly treatise on the nature of health presented in the form of a dialogue between an inquirer and a philosopher. It attempts to do two things: first, to introduce modern philosophy of health to non-philosophers, in particular to people with a professional relation to health care; and second, to elaborate and specify in some detail the author's holistic theory of health. According to this theory, a person is completely healthy if, and only if, she or he is able to realize all her or his vital goals given reasonable circumstances. This theory is presented by the philosopher in the book, but it is at the same time scrutinized and criticized by the inquirer. Some of the criticisms presented, and to which the philosopher responds, have been put forward in published reviews of the author's earlier works. Towards the end of the book the author demonstrates how his philosophy of health can be applied to related areas, such as the theory of disability, and to modern ethical discussion, such as that concerning prioritization in health care. The book is supplemented with a list of definitions of central concepts and with an annotated bibliography.